Composite material with heat conduction effect as well as preparation method and application of composite material

By using modified thermal fillers in polyamide resin, the problem of low thermal conductivity of polyamide-66 material is solved, and the thermal conductivity and electromagnetic shielding performance of composite materials are significantly improved.

CN119798968AActive Publication Date: 2025-04-11LINGGU NEW MATERIALS (GUANGDONG) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510043505.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing polyamide-66 materials have low thermal conductivity and need to improve thermal conductivity to suit a wider range of applications.

Method used

By adding a modified thermally conductive filler to the polyamide resin, the specific method includes stirring boron nitride and carbon nanotubes with water and sodium lignin sulfonate, then adding cerium nitrate and sodium hydroxide to react, and processing at high temperature, and finally adding a modifier for further processing to prepare the modified thermally conductive filler.

Benefits of technology

The thermal conductivity and electromagnetic shielding properties of composite materials are significantly improved, making them suitable for a wider range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237642790000091
    Figure BDA0005237642790000091
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and particularly discloses a composite material with a heat conduction effect as well as a preparation method and application thereof. The composite material with the heat conduction effect comprises the following raw material components in parts by weight: 80-150 parts of polyamide resin; 20-40 parts of a heat-conducting filler; 5-15 parts of a flame retardant; 1-5 parts of a dispersant; and 1-3 parts of an antioxidant. Researches show that the composite material with the heat conduction effect has good heat conduction performance, also has good electromagnetic shielding performance and has important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a composite material with heat conduction function and a preparation method and application thereof. Background Art

[0002] Polyamide resin is usually a polycondensation polymer compound with a -CONH structure in the molecule obtained by polycondensation of dibasic acid and diamine. Among them, polyamide-66 is one of the commonly used polyamide resins, also known as nylon-66; due to its high tensile strength, good wear resistance and electrical insulation properties, it can be used as an engineering plastic, and can also be blended or spun into various medical and knitwear. However, pure polyamide-66 has a low thermal conductivity and poor thermal conductivity, which needs to be further improved.

[0003] Chinese invention patent CN201410376775.9 discloses a hyperbranched polyamide composite filled polymer-based thermally conductive plastic and its preparation method; the mass percentage of various raw materials is: 20-90% matrix resin, 10-80% thermally conductive filler, and in addition, it also contains 0.2-1% toughening agent, 1-3% coupling agent, 0.1-0.5% antioxidant, and 0.1-1.5% lubricant in total; the matrix resin is a hyperbranched polyamide (HPA) and nylon PA66 with a mass ratio of 1-9:1; the thermally conductive filler is a mixture of large and small particle sizes of magnesium oxide. Although the thermally conductive plastic prepared by this invention can achieve good thermal conductivity, it needs to add more than 60% of thermally conductive filler to achieve it; it needs further improvement. Summary of the invention

[0004] In order to overcome at least one of the technical problems existing in the prior art, the present invention provides a composite material with thermal conductivity, a preparation method and application thereof.

[0005] The present invention first provides a composite material with a thermal conductivity, which comprises the following raw material components in parts by weight:

[0006] 80-150 parts of polyamide resin; 20-40 parts of thermal conductive filler; 5-15 parts of flame retardant; 1-5 parts of dispersant; 1-3 parts of antioxidant.

[0007] The present invention adds a thermally conductive filler of a completely new composition into the polyamide resin, so that the prepared composite material has a thermal conductive effect.

[0008] In addition, the present invention can also help improve the flame retardant performance of the polyamide resin by adding a flame retardant.

[0009] Preferably, the composite material having a thermal conductive effect comprises the following raw material components in parts by weight:

[0010] 100-120 parts of polyamide resin; 20-30 parts of thermal conductive filler; 5-10 parts of flame retardant; 1-3 parts of dispersant; 1-2 parts of antioxidant.

[0011] Most preferably, the composite material having thermal conductivity comprises the following raw material components in parts by weight:

[0012] 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant; 3 parts of dispersant; 2 parts of antioxidant.

[0013] Preferably, the thermally conductive filler consists of boron nitride and carbon nanotubes.

[0014] The present invention adds a thermally conductive filler composed of boron nitride and carbon nanotubes, which can make the prepared composite material have a better thermal conductive effect.

[0015] Preferably, the weight ratio of boron nitride to carbon nanotubes in the thermal conductive filler is 3 to 5:1.

[0016] Most preferably, the weight ratio of boron nitride to carbon nanotubes in the thermally conductive filler is 4:1.

[0017] Preferably, the thermally conductive filler is a modified thermally conductive filler;

[0018] The modified thermally conductive filler is prepared by the following method:

[0019] Add boron nitride and carbon nanotubes into water, then add sodium lignin sulfonate and stir evenly to obtain a boron nitride-carbon nanotube mixed solution;

[0020] Add cerium nitrate to the boron nitride-carbon nanotube mixture, then add sodium hydroxide, stir and react for 2 to 4 hours, then separate the solid to obtain product A;

[0021] The product A is subjected to constant temperature treatment at 300-500° C. for 1-3 hours to obtain the product B; the product B is taken to obtain the modified thermal conductive filler.

[0022] The inventors surprisingly found in further research that adding a modified thermal conductive filler prepared by modifying boron nitride and carbon nanotubes by the above method to a polyamide resin can significantly improve the thermal conductivity of the prepared composite material, compared with adding an unmodified thermal conductive filler composed of boron nitride and carbon nanotubes.

[0023] In addition, the inventors surprisingly found in further research that adding a modified thermal conductive filler prepared by modifying boron nitride and carbon nanotubes by the above method to a polyamide resin can significantly improve the electromagnetic shielding performance of the prepared composite material, compared with adding an unmodified thermal conductive filler composed of boron nitride and carbon nanotubes.

[0024] Preferably, the carbon nanotubes are multi-walled carbon nanotubes.

[0025] Preferably, the usage ratio of boron nitride, carbon nanotubes and water is 3-5 kg: 1 kg: 25-50 L.

[0026] Most preferably, the usage ratio of boron nitride, carbon nanotubes and water is 4kg:1kg:30L.

[0027] Preferably, the usage ratio of sodium lignin sulfonate to water is 0.3-1 kg:25-50 L.

[0028] Most preferably, the dosage ratio of sodium lignin sulfonate to water is 0.6kg:30L.

[0029] Preferably, the usage ratio of the boron nitride-carbon nanotube mixed solution to cerium nitrate and sodium hydroxide is 25-50 L: 0.3-0.5 kg: 1.2-2.5 kg.

[0030] Most preferably, the usage ratio of the boron nitride-carbon nanotube mixed solution to cerium nitrate and sodium hydroxide is 30L:0.35kg:1.5kg.

[0031] Further preferably, the modified thermally conductive filler further comprises the following steps:

[0032] The product B is added into water, and then a modifier is added, and after stirring at 40-80° C. for 3-5 hours, the solid is separated and dried to obtain the modified thermal conductive filler.

[0033] The inventors found in further research that adding a modified thermal conductive filler obtained by further treating the polyamide resin with a modifier can further improve or significantly improve the thermal conductivity and electromagnetic shielding performance of the prepared composite material, compared with the modified thermal conductive filler not treated with a modifier.

[0034] Preferably, the usage ratio of the product B to the modifier and water is 1kg:0.2-0.4kg:4-8L.

[0035] Most preferably, the usage ratio of the product B to the modifier and water is 1kg:0.3kg:6L.

[0036] The modifier is selected from one or a combination of bis(dioctyloxypyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate.

[0037] The modifier consists of bis(dioctyloxypyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate.

[0038] Preferably, the weight ratio of bis(dioctyloxypyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzenesulfonate is 1-3:3-6:1-3.

[0039] Most preferably, the weight ratio of bis(dioctyloxypyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzenesulfonate is 2:5:2.

[0040] The inventors found in further research that the selection of the modifier of the present invention is very critical. The modified thermal conductive filler obtained by further treating the polyamide resin with a single modifier, bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate or sodium dodecylbenzene sulfonate, can further improve the thermal conductivity and electromagnetic shielding performance of the prepared composite material compared to the modified thermal conductive filler obtained without the modifier treatment; but the improvement is not large. Only by adding the modified thermal conductive filler obtained by further treating the polyamide resin with a modifier composed of bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate, can the thermal conductivity of the prepared composite material be further significantly improved and the electromagnetic shielding performance of the prepared composite material be further significantly improved.

[0041] Preferably, the flame retardant is selected from aluminum hydroxide or magnesium hydroxide.

[0042] Preferably, the dispersant is selected from ethylene bisstearamide.

[0043] Preferably, the antioxidant is selected from antioxidant 1010.

[0044] The present invention also provides a method for preparing the composite material having a thermal conductive effect, which comprises the following steps:

[0045] The polyamide resin, thermal conductive filler, flame retardant, dispersant and antioxidant are mixed uniformly, and then melt-extruded through a twin-screw extruder to obtain the composite material with thermal conductivity.

[0046] Beneficial effects: The present invention provides a composite material with a new composition and a thermal conductive function; studies have shown that the composite material with a thermal conductive function of the present invention not only has good thermal conductivity, but also has good electromagnetic shielding performance, and has important application value. DETAILED DESCRIPTION

[0047] The present invention is further explained below in conjunction with specific embodiments, but the specific embodiments do not limit the present invention in any form.

[0048] The polyamide resin used in the following examples is polyamide resin with a brand number of 101L produced by DuPont Company of the United States; the other raw materials whose sources are not specified are all conventional raw materials that can be purchased in the art.

[0049] Example 1 Preparation of a composite material having a thermal conductivity

[0050] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0051] The thermal conductive filler is composed of boron nitride and multi-walled carbon nanotubes in a weight ratio of 4:1.

[0052] Preparation method: polyamide resin, thermal conductive filler, flame retardant, dispersant and antioxidant are mixed evenly, and then melt-extruded through a twin-screw extruder to obtain the composite material with thermal conductivity.

[0053] Example 2 Preparation of a composite material having a thermal conductivity

[0054] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0055] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0056] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0057] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0058] (3) The product A is subjected to a constant temperature treatment at 400° C. for 2 h to obtain the product B; the product B is taken to obtain the modified thermal conductive filler.

[0059] Example 3 Preparation of composite material with thermal conductivity

[0060] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0061] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0062] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0063] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0064] (3) treating product A at 400°C for 2 h to obtain product B;

[0065] (4) Add product B to water, then add a modifier, stir at 60° C. for 4 hours, separate the solid, and dry the solid to obtain the modified thermal conductive filler; wherein the amount ratio of product B to the modifier and water is 1kg:0.3kg:6L; and the modifier is bis(dioctyloxypyrophosphate)ethylene titanate.

[0066] Example 4 Preparation of a composite material having a thermal conductivity

[0067] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0068] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0069] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0070] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0071] (3) treating product A at 400°C for 2 h to obtain product B;

[0072] (4) Add product B to water, then add a modifier, stir at 60° C. for 4 hours, separate the solid, and dry the solid to obtain the modified thermal conductive filler; wherein the amount ratio of product B to the modifier and water is 1kg:0.3kg:6L; and the modifier is ammonium pentafluorooctanoate.

[0073] Example 5 Preparation of a composite material having a thermal conductivity

[0074] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0075] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0076] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0077] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0078] (3) treating product A at 400°C for 2 h to obtain product B;

[0079] (4) Add product B to water, then add a modifier, stir at 60° C. for 4 hours, separate the solid, and dry the solid to obtain the modified thermal conductive filler; wherein the amount ratio of product B to the modifier and water is 1kg:0.3kg:6L; and the modifier is sodium dodecylbenzene sulfonate.

[0080] Example 6 Preparation of a composite material having a thermal conductivity

[0081] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0082] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0083] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0084] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0085] (3) treating product A at 400°C for 2 h to obtain product B;

[0086] (4) Add product B to water, then add a modifier, stir at 60° C. for 4 hours, separate the solid, and dry the solid to obtain the modified thermal conductive filler; wherein the amount ratio of product B to the modifier and water is 1 kg:0.3 kg:6 L; the modifier is composed of bis(dioctyloxypyrophosphate)ethylene titanate and ammonium pentafluorooctanoate in a weight ratio of 2:5.

[0087] Example 7 Preparation of a composite material having a thermal conductivity

[0088] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0089] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0090] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0091] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0092] (3) treating product A at 400°C for 2 h to obtain product B;

[0093] (4) Add product B to water, then add a modifier, stir at 60° C. for 4 hours, separate the solid, and dry the solid to obtain the modified thermal conductive filler; wherein the amount ratio of product B to the modifier and water is 1 kg:0.3 kg:6 L; the modifier is composed of bis(dioctyloxypyrophosphate)ethylene titanate and sodium dodecylbenzene sulfonate in a weight ratio of 1:1.

[0094] Example 8 Preparation of a composite material having a thermal conductivity

[0095] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0096] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0097] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0098] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0099] (3) treating product A at 400°C for 2 h to obtain product B;

[0100] (4) Add product B to water, then add a modifier, stir at 60° C. for 4 hours, separate the solid, and dry the solid to obtain the modified thermal conductive filler; wherein the amount ratio of product B to the modifier and water is 1kg:0.3kg:6L; the modifier is composed of ammonium pentadecafluorooctanoate and sodium dodecylbenzene sulfonate in a weight ratio of 5:2.

[0101] Example 9 Preparation of a composite material having a thermal conductivity

[0102] Raw materials are composed by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant (magnesium hydroxide); 3 parts of dispersant (ethylene bisstearamide); 2 parts of antioxidant (antioxidant 1010);

[0103] The thermally conductive filler is a modified thermally conductive filler; the modified thermally conductive filler is prepared by the following method:

[0104] (1) adding boron nitride and multi-walled carbon nanotubes to water, and then adding sodium lignin sulfonate and stirring to obtain a boron nitride-carbon nanotube mixed solution; wherein the amount ratio of boron nitride, multi-walled carbon nanotubes to water is 4kg:1kg:30L; and the amount ratio of sodium lignin sulfonate to water is 0.6kg:30L;

[0105] (2) adding cerium nitrate to the boron nitride-carbon nanotube mixed solution, and then adding sodium hydroxide, stirring the reaction for 3 hours, and then separating the solid to obtain product A; wherein the amount ratio of the boron nitride-carbon nanotube mixed solution to the cerium nitrate and the sodium hydroxide is 30L:0.35kg:1.5kg;

[0106] (3) treating product A at 400°C for 2 h to obtain product B;

[0107] (4) Add product B to water, then add a modifier, stir at 60° C. for 4 hours, separate the solid, and dry the solid to obtain the modified thermal conductive filler; wherein the amount ratio of product B to the modifier and water is 1 kg:0.3 kg:6 L; the modifier is composed of bis(dioctyloxypyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate in a weight ratio of 2:5:2.

[0108] The thermal conductivity of the composite materials with thermal conductivity prepared in Examples 1 to 9 was tested according to the method in ASTM E1461-2013 standard; the electromagnetic shielding effectiveness was tested according to the method in ASTM D4935 standard; the test results are shown in Table 1.

[0109] Table 1. Performance test results of the composite material with thermal conductivity of the present invention

[0110]

[0111] It can be seen from the experimental results in Table 1 that the thermal conductivity of the composite material with thermal conductivity prepared in Example 1 reaches 1.98 W / (m·K); this shows that the composite material with thermal conductivity prepared in the present invention has good thermal conductivity.

[0112] It can be seen from the experimental results in Table 1 that the thermal conductivity of the composite material with thermal conductivity prepared in Example 2 is significantly higher than that of the composite material with thermal conductivity prepared in Example 1; this indicates that adding the modified thermal conductive filler prepared by modifying boron nitride and carbon nanotubes by the method of the present invention to the polyamide resin can significantly improve the thermal conductivity of the prepared composite material, compared with adding the unmodified thermal conductive filler composed of boron nitride and carbon nanotubes.

[0113] It can be seen from the experimental results in Table 1 that the thermal conductivity of the composite materials with thermal conductivity prepared in Examples 3 to 9 is further higher or significantly higher than that of the composite materials with thermal conductivity prepared in Example 2; this indicates that the modified thermal conductive filler obtained by further treating the polyamide resin with a modifier can further improve or significantly improve the thermal conductivity of the prepared composite material compared to the modified thermal conductive filler obtained without treating the modifier.

[0114] It can be seen from the experimental results in Table 1 that the thermal conductivity of the composite materials with thermal conductivity prepared in Examples 3 to 8 is improved compared with that of the composite materials with thermal conductivity prepared in Example 2, but the improvement is not large; the improvement is much smaller than that of the composite materials with thermal conductivity prepared in Example 9. This shows that: the selection of the modifier of the present invention is very critical; the modified thermal conductive filler obtained by further treating the polyamide resin with a single modifier, bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate or sodium dodecylbenzene sulfonate, or the modified thermal conductive filler obtained by treating the polyamide resin with a modifier composed of any two of bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate cannot further significantly improve the thermal conductivity of the prepared composite material compared to the modified thermal conductive filler obtained without the modifier treatment; only by adding the modified thermal conductive filler obtained by further treating the polyamide resin with a modifier composed of bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate, can the thermal conductivity of the prepared composite material be further significantly improved.

[0115] It can be seen from the experimental results in Table 1 that the composite material with thermal conductivity prepared in Example 1 has an electromagnetic shielding effectiveness of 30.8 dB; this indicates that the composite material with thermal conductivity prepared in the present invention has an electromagnetic shielding effect.

[0116] It can be seen from the experimental results in Table 1 that the electromagnetic shielding performance of the composite material with thermal conductivity prepared in Example 2 is further significantly higher than that of the composite material with thermal conductivity prepared in Example 1; this indicates that adding the modified thermal conductive filler prepared by modifying boron nitride and carbon nanotubes by the method of the present invention to the polyamide resin can greatly improve the electromagnetic shielding effect of the prepared composite material, compared with adding the unmodified thermal conductive filler composed of boron nitride and carbon nanotubes.

[0117] It can be seen from the experimental results in Table 1 that the electromagnetic shielding effectiveness of the composite materials with thermal conductivity prepared in Examples 3 to 9 is further higher than or significantly higher than that of the composite materials with thermal conductivity prepared in Example 2; this means that the modified thermal conductive filler obtained by further treating the polyamide resin with a modifier can further improve or significantly improve the electromagnetic shielding effectiveness of the prepared composite material, compared with the modified thermal conductive filler not treated with a modifier.

[0118] It can be seen from the experimental results in Table 1 that the electromagnetic shielding effectiveness of the composite materials with thermal conductivity prepared in Examples 3 to 8 is improved compared with that of the composite materials with thermal conductivity prepared in Example 2, but the improvement is not large; the improvement is much smaller than that of the composite materials with thermal conductivity prepared in Example 9. This shows that: the selection of the modifier of the present invention is very critical; the modified thermal conductive filler obtained by adding a single modifier bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate or sodium dodecylbenzene sulfonate to the polyamide resin, or the modified thermal conductive filler obtained by adding a modifier composed of any two of bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate to the polyamide resin, compared with the modified thermal conductive filler obtained without the modifier treatment, it cannot further significantly improve the electromagnetic shielding effectiveness of the prepared composite material; only by adding a modified thermal conductive filler obtained by further treating with a modifier composed of bis(dioctyl pyrophosphate)ethylene titanate, ammonium pentafluorooctanoate and sodium dodecylbenzene sulfonate to the polyamide resin, can the electromagnetic shielding effectiveness of the prepared composite material be further significantly improved.

Claims

1. A composite material with thermal conductivity, characterized in that: The raw material components include the following parts by weight: 80-150 parts of polyamide resin; 20-40 parts of thermal conductive filler; 5-15 parts of flame retardant; 1-5 parts of dispersant; 1-3 parts of antioxidant.

2. The composite material with thermal conductivity according to claim 1, characterized in that: The raw material components include the following parts by weight: 100-120 parts of polyamide resin; 20-30 parts of thermal conductive filler; 5-10 parts of flame retardant; 1-3 parts of dispersant; 1-2 parts of antioxidant.

3. The composite material with thermal conductivity according to claim 1, characterized in that: The raw material components include the following parts by weight: 110 parts of polyamide resin; 25 parts of thermal conductive filler; 10 parts of flame retardant; 3 parts of dispersant; 2 parts of antioxidant.

4. The composite material with thermal conductivity according to claim 1, characterized in that: The thermal conductive filler consists of boron nitride and carbon nanotubes.

5. The composite material with thermal conductivity according to claim 4, characterized in that: The weight ratio of boron nitride to carbon nanotubes in the thermal conductive filler is 3 to 5:

1. Most preferably, the weight ratio of boron nitride to carbon nanotubes in the thermally conductive filler is 4:

1.

6. The composite material with thermal conductivity according to claim 4, characterized in that: The thermally conductive filler is a modified thermally conductive filler; The modified thermally conductive filler is prepared by the following method: Add boron nitride and carbon nanotubes into water, then add sodium lignin sulfonate and stir evenly to obtain a boron nitride-carbon nanotube mixed solution; Add cerium nitrate to the boron nitride-carbon nanotube mixture, then add sodium hydroxide, stir and react for 2 to 4 hours, then separate the solid to obtain product A; The product A is subjected to constant temperature treatment at 300-500° C. for 1-3 hours to obtain the product B; the product B is taken to obtain the modified thermal conductive filler.

7. The composite material with thermal conductivity according to claim 6, characterized in that: The usage ratio of boron nitride, carbon nanotubes and water is 3-5kg:1kg:25-50L. Most preferably, the usage ratio of boron nitride, carbon nanotubes and water is 4kg:1kg:30L.

8. The composite material with thermal conductivity according to claim 6, characterized in that: The dosage ratio of sodium lignin sulfonate to water is 0.3-1kg:25-50L. Most preferably, the dosage ratio of sodium lignin sulfonate to water is 0.6kg:30L.

9. The composite material with thermal conductivity according to claim 6, characterized in that: The dosage ratio of the boron nitride-carbon nanotube mixed solution to cerium nitrate and sodium hydroxide is 25-50L: 0.3-0.5kg: 1.2-2.5kg.

10. The method for preparing the composite material with thermal conductivity according to any one of claims 1 to 9, characterized in that: The following steps are included: The polyamide resin, thermal conductive filler, flame retardant, dispersant and antioxidant are mixed uniformly, and then melt-extruded through a twin-screw extruder to obtain the composite material with thermal conductivity.

Citation Information

Patent Citations

  • Hyperbranched polyamide composite filled polymer-based thermal conductive plastic and preparation method thereof

    CN104177842A

  • Polyamide composite material with high thermal conductivity and high heat resistance and preparation method thereof

    CN104371318A

  • Hydrolysis resistance aluminum nitride filled polyamide based heat conduction plastic and preparation method thereof

    CN104448799A

  • High performance heat conductive plastic used for LED

    CN108314893A

  • Modified carbon nanotube as well as preparation method and application thereof

    CN109370266A